Profil Mutu dan Uji Hedonik Sosis Analog Berbasis Tepung Koro Pedang (Canavalia ensiformis) dan Tepung Wortel (Daucus carota L.) - Utami, Angestri Dyah; Kumalasari, Ika Dyah (Jurnal Teknologi Hasil Pertanian, 2025)
Excessive consumption of animal-based food products can increase the risk of chronic degenerative diseases. Plant-based analog sausages are presented as an alternative. This study developed analog sausages using jack bean flour as a protein source and carrots to enrich fiber content and antioxidant activity. The aim of this research was to determine the optimal analog sausage formulation based on hedonic test, as well as to evaluate its physicochemical properties and Total Plate Count (TPC). The research used a Completely Randomized Design (CRD) with three replications. The analog sausage formulations consisted of varying ratios of sword bean flour to carrot flour: F1 (75%:25%), F2 (60%:40%), F3 (50%:50%), and F4 (25%:50%). Observations included physical properties (texture), chemical properties (moisture, ash, protein, carbohydrate, fat, crude fiber, and antioxidant activity), TPC, and sensory attributes through hedonic tests. Data were analyzed using ANOVA and followed by Duncan's multiple range test. The results showed that the combination of jack bean flour and carrot flour significantly affected the physical, chemical, and sensory properties. The F3 formulation (50%:50%) achieved the highest scores in the hedonic test with an overall acceptance of 3.46, taste 3.56, aroma 3.53, and gumminess 4.31 N. F1 (75%:25%) showed the highest values in hardness (36.8 N), protein content (4.14%), and fat content (3.55%). F2 (60%:40%) had the highest moisture content at 50.86%. Meanwhile, F4 (25%:50%) showed the highest springiness (0.63), chewiness (2.42 N), ash content (3.57%), carbohydrate content (40.63%), crude fiber (3.3%), and antioxidant activity (27.37%). The TPC results met the Indonesian National Standard (SNI) 3820:2015, with values ranging from (1.96 – 3.56) x 10² CFU/g.